Pregnant women and midwives' perception regarding physical activity recommendation during pregnancy. (20th October 2021) - Scognamiglio, F; Soldà, G; Marini, S; Masini, A; Messina, R; Caravita, I; Leccese, V; Bertini, V; Parma, D; Dallolio, L
Abstract: Introduction: Physical activity (PA) is a modifiable lifestyle factor which contributes to improve pregnancy and perinatal outcomes. Therefore, pregnant women (PW) without contraindications should practice 150 minutes of moderate PA per week, according to the World Health Organization (WHO) guidelines. Nevertheless, a reduction of PA throughout the gestational period appears to be worryingly common. The aim of this survey was to analyse the feasibility of the WHO recommendations, investigating PW and midwives' perceptions towards PA during pregnancy, in a view to enhance future PA interventions. Methods: A total number of 4 focus groups, involving 10 midwives (aged 43-61) and 10 PW (aged 30-46), recruited at the University Hospital of Bologna, were carried out between July 2020 and April 2021. Due to SARS-CoV-2 restrictions, all meetings were held online, recorded, transcribed and then analysed using the COM-B model. Results: WHO recommendations were deemed feasible by both midwives and PW when time management skills and capabilities to adapt PA to individual needs were present. Clearly, women with a background in PA practice tend to be highly motivated thereby maintaining the PA routine also during pregnancy. Both groups reported that PA represents a positive element for the mother's and baby's well-being, triggering a virtuous circle and increasing motivation. Being able to access and perform simple, structured, evidence-based activities, family support, and using every opportunity to be less sedentary were reported as key aspects amongst opportunities to improve PA levels. Conclusions: Positive perception regarding feasibility of the recommendations was similar between groups; nevertheless, midwives perceived pregnancy as an opportunity to change PA routines, while PW considered pregnancy a less dynamic period. Therefore, implementing PA promotion involving midwives might represent a good strategy given their central role during this woman' unique period. Key messages: WHO physical activity recommendations are overall deemed feasible, but tailored opportunities and strategies tackling everyday obstacles and lack of information need to be provided. Enhancing PA is a key challenge for pregnant women in a view of their own and baby's health. The COM-B model can be used to implement new strategies involving midwives to reach the goal.